Influence of corporate financial education on decision-making in olive processing processors and derivatives Tacna region, 2016 - Wong Copaja, Edgard Enrique (2016)
Objective: The purposeofthis thesis was to determine the influence of corporate financial education on decision - making in olive - processing entrepreneurs and derivatives Region Tacna, 2016. Methodology: The type of research is pure, because it is oriented to achieve a new knowledge in the field of finance. The present research responds to an explanatory causal descriptive research design. The population is conformed by all the managers of processing companies of Olive and Derivatives of the Agro Industrial Sector of the region of Tacna. The sample is census and takes the 15 managers of processing companies of Olive and Derivatives of the Agro Industrial Sector of the Region of Tacna that are registered in the Chamber of Commerce of Tacna. The technique for the collection of the data for the present investigation was the survey. The instrument that was applied was the questionnaire with the Likert scale. Statistical analysis was applied Chi-Square, and other measures of central tendency. Results: The results found in the research were that 53.3% of the olive and derivative processors do not have a corporate financial education and 60% of the entrepreneurs still make empirical decisions. Conclusion: As a conclusion of this thesis, the processors of olives and derivatives from the region of Tacna do not have adequate corporate financial education and this is a consequence of not being able to make budgets, debt management, investment, Saving.